Exorcising the antiquity spirit of intolerance : possibilities and dilemmas of decriminalising sodomy laws in Uganda - De Vos, Pierre (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2007.